THE EFFECT OF COMMUNICATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT PARAMADINA UNIVERSITY IN JAKARTA - Hadi Wibowo; Dewi Listiorini; Arif Haryadi (SEAN Institute, 2023)
Primary communication is the process of conveying one's thoughts and or feelings to others. Organizational culture can influence human behavior in organizations, especially in terms of trust and commitment in the organization. Employee performance is the scope of responsibility, of course referring to the work results that have been achieved by someone related to work. The research objectives are as follows: To find out whether together the influence of Communication and Organizational Culture on Employee Performance at Paramadina University in Jakarta. The sampling technique used in this study the authors used the Random Sampling technique or by random method, all employees were a population of 179 and were used as a random sample using the Slovin formula in Husein Umar, 2015, only 64 samples were obtained. The results showed that partially and simultaneously there is a positive and significant influence between Communication and Organizational Culture on Employee Performance.